(untitled) (Prilozi za orijentalnu filologiju, 2024)
Thus far, in dealing with the issue of agrarian relations in 16th-century Otto- man Bosnia the focus has been on the miri land regime, that is, on the state ownership, with a concession made for a different type like the vakıf or mülk land. Some attention was occasionally paid to phenomena such as land lease in the early phase, lump-sum paying, and gradual spread of çiftliks as an occurrence that was running against the classic regime and the like. Thereby a simple fact was overlooked, i.e., the “silent”, but necessary presence of a kind of relationship that must have coexisted with the miri regime without contradicting it. This was the very important fact rooted in the question of the volume of agrarian output, mainly the grain. From village to village the grain to people ratio was uneven: sometimes there was enough per capita, but often it was much above or much below the needs of the community as expressed by the social minimum. Here opens the possibility of taking the “surplus” in the shape of a rate higher than the tithe (or one eight) on the basis of private agreement, outside the scope of the Sacred Law. In order to present this matter in broader outline a comparison was necessary with other parts of the Empire (East Central Anatolia, Southern Syria and Palestine) where rates up to one half of the produce were in vigor according to local regulations with religious approval. The apparently diametrically opposite to each other, the two ap- proaches had still much in common “here” and “there”.